Habitat-specific shape variation in the carapace of the crab Cyrtograpsus angulatus - Idaszkin, Yanina Lorena (2013)
Different environmental and sex conditions induce phenotypic responses (behavioural, morphological and physiological) in many species. The crab Cyrtograpsus angulatus inhabits contrasting intertidal habitats, such as rocky shores and salt marshes, where they are exposed to a wide diversity of predators. However, their anti-predator responses differ substantially between these two habitats: while crabs in the salt marshes use or built burrows or they simply hide by burying in the sediment into the tidal channels, on rocky shores they find shelter below rocks, inside crevices or under seaweeds in tidal pools. Considering that refuges in salt marshes can be adjusted by the crabs according to their size and the morphology, while in rocky shores they have to fit in the available refuges, we expect that the body shape differs between individuals from each intertidal habitat. In order to test this hypothesis, we collected male and female crabs from a salt marsh and a rocky shore, separated by 3km, in San José Gulf, Patagonia, and compared the carapace shapes using geometric morphometric methods. The results showed that carapace shape variation is explained by the interaction between sex and habitats. In both sexes, the mean carapace shape on the rocky shore is more slender and more lengthened than in the salt marsh individuals. Furthermore, the posterior margin of the female carapaces was wider than that of male carapaces, which were slender and more rounded posterolaterally, independent of the intertidal habitat.